Beispiel Nr: 24
$ \text{Gegeben:} \\ \text{Lineares Gleichungssytem} \\ a1 \cdot x_1 + b1\cdot x_2 + c1\cdot x_3 ....=d1 \\ a2\cdot x_1 + b2\cdot x_2 + c2\cdot x_3 .....=d2\\ a3\cdot x_1 + b3\cdot x_2 + c3\cdot x_3....=d3\\ ..... \\ \text{Gesucht: }x_1,x_2,x_3.... \\ \\ $
$\textbf{Aufgabe:}$ x
$\textbf{Rechnung:}\\ \small \begin{array}{l} 4x_1+x_2+8x_3=2 \\ 8x_1+x_2+x_3=1 \\ 3x_1+6x_2+2x_3=10 \\ \\ \end{array} \qquad \small \begin{array}{ccc|cc } x_1 & x_2 & x_3 & & \\ \hline4 & 1 & 8 & 2 \\ 8 & 1 & 1 & 1 \\ 3 & 6 & 2 & 10 \\ \end{array} \\ \\ \small \begin{array}{l}\text{Zeile}2=\text{Zeile}2\text{-Zeile}1\cdot \frac{8}{4}\\z2s1=8-4\cdot \frac{8}{4}=0 \\ z2s2=1-1\cdot \frac{8}{4}=-1 \\ z2s3=1-8\cdot \frac{8}{4}=-15 \\ z2s4=1-2\cdot \frac{8}{4}=-3 \\ \end{array}\qquad \small \begin{array}{ccc|cc } x_1 & x_2 & x_3 & & \\ \hline4 & 1 & 8 & 2 \\ 0 & -1 & -15 & -3 \\ 3 & 6 & 2 & 10 \\ \end{array} \\ \\ \small \begin{array}{l}\text{Zeile}3=\text{Zeile}3\text{-Zeile}1\cdot \frac{3}{4}\\z3s1=3-4\cdot \frac{3}{4}=0 \\ z3s2=6-1\cdot \frac{3}{4}=5\frac{1}{4} \\ z3s3=2-8\cdot \frac{3}{4}=-4 \\ z3s4=10-2\cdot \frac{3}{4}=8\frac{1}{2} \\ \end{array}\qquad \small \begin{array}{ccc|cc } x_1 & x_2 & x_3 & & \\ \hline4 & 1 & 8 & 2 \\ 0 & -1 & -15 & -3 \\ 0 & 5\frac{1}{4} & -4 & 8\frac{1}{2} \\ \end{array} \\ \\ \small \begin{array}{l}\text{Zeile}1=\text{Zeile}1\text{-Zeile}2\cdot \frac{1}{-1}\\z1s2=1-(-1)\cdot \frac{1}{-1}=0 \\ z1s3=8-(-15)\cdot \frac{1}{-1}=-7 \\ z1s4=2-(-3)\cdot \frac{1}{-1}=-1 \\ \end{array}\qquad \small \begin{array}{ccc|cc } x_1 & x_2 & x_3 & & \\ \hline4 & 0 & -7 & -1 \\ 0 & -1 & -15 & -3 \\ 0 & 5\frac{1}{4} & -4 & 8\frac{1}{2} \\ \end{array} \\ \\ \small \begin{array}{l}\text{Zeile}3=\text{Zeile}3\text{-Zeile}2\cdot \frac{5\frac{1}{4}}{-1}\\z3s2=5\frac{1}{4}-(-1)\cdot \frac{5\frac{1}{4}}{-1}=0 \\ z3s3=-4-(-15)\cdot \frac{5\frac{1}{4}}{-1}=-82\frac{3}{4} \\ z3s4=8\frac{1}{2}-(-3)\cdot \frac{5\frac{1}{4}}{-1}=-7\frac{1}{4} \\ \end{array}\qquad \small \begin{array}{ccc|cc } x_1 & x_2 & x_3 & & \\ \hline4 & 0 & -7 & -1 \\ 0 & -1 & -15 & -3 \\ 0 & 0 & -82\frac{3}{4} & -7\frac{1}{4} \\ \end{array} \\ \\ \small \begin{array}{l}\text{Zeile}1=\text{Zeile}1\text{-Zeile}3\cdot \frac{-7}{-82\frac{3}{4}}\\z1s3=-7-(-82\frac{3}{4})\cdot \frac{-7}{-82\frac{3}{4}}=0 \\ z1s4=-1-(-7\frac{1}{4})\cdot \frac{-7}{-82\frac{3}{4}}=-0,387 \\ \end{array}\qquad \small \begin{array}{ccc|cc } x_1 & x_2 & x_3 & & \\ \hline4 & 0 & 0 & -0,387 \\ 0 & -1 & -15 & -3 \\ 0 & 0 & -82\frac{3}{4} & -7\frac{1}{4} \\ \end{array} \\ \\ \small \begin{array}{l}\text{Zeile}2=\text{Zeile}2\text{-Zeile}3\cdot \frac{-15}{-82\frac{3}{4}}\\z2s3=-15-(-82\frac{3}{4})\cdot \frac{-15}{-82\frac{3}{4}}=0 \\ z2s4=-3-(-7\frac{1}{4})\cdot \frac{-15}{-82\frac{3}{4}}=-1,69 \\ \end{array}\qquad \small \begin{array}{ccc|cc } x_1 & x_2 & x_3 & & \\ \hline4 & 0 & 0 & -0,387 \\ 0 & -1 & 0 & -1,69 \\ 0 & 0 & -82\frac{3}{4} & -7\frac{1}{4} \\ \end{array} \\ \\ x_1=\frac{-0,387}{4}=-0,0967\\x_2=\frac{-1,69}{-1}=1,69\\x_3=\frac{-7\frac{1}{4}}{-82\frac{3}{4}}=0,0876\\L=\{-0,0967/1,69/0,0876\}$